The effects of a small hydropower scheme on the migratory behaviour of Atlantic salmon Salmo salar smolts. Issue 3 (26th September 2018) - Moore, Andy; Privitera, Lucia; Ives, Mark J.; Uzyczak, Jane; Beaumont, William R. C.
Abstract : The potential effects of a hydropower scheme on the migratory behaviour of Atlantic salmon Salmo salar smolts was studied on the River Frome, southern England. The potential delay to migration at the intake of the hydropower scheme was assessed, together with the effects of passage through the turbine on the temporal and spatial migration of the fish in the river and estuary. The migratory behaviour of the emigrating S. salar smolts was monitored using miniature acoustic transmitters and an array of acoustic receivers positioned at the hydropower scheme and in the river and estuary. The majority of the smolts bypassed the hydropower scheme with only 8.1% of the fish moving downstream through the turbine. Movement was nocturnal and occurred during elevated river flows. There was no apparent delay at the turbine intake or at the adjacent weir. The subsequent migration of all smolts through the estuary of the River Frome occurred during both day and night and there was a distinct ebb‐tide migration through the estuary and into the coastal zone. There was no difference in the rate of migration between smolts that moved through the turbine or over the weir. The detection of smolts during both the freshwater migration and the transition from the freshwater to the marine environments was high (91.8 and 73.3%, respectively). A laboratory investigation on the de‐scaling of smolts indicated that removal of 1, 5 and 10% of scales had no significant effect on saltwater survival or the measured physiological parameters (gill Na + –K + ‐ATPase activity, plasma osmolality and chloride concentrations). Smolt passage through the turbine was assessed and resulted in either no damage to the integument or scale loss or between 20 and 80% of total body area of recaptured smolts. It is estimated that 1.53% of the smolt population would suffer significant damage after passage through the turbine. The implications of the hydropower scheme on the population of salmon in the River Frome are discussed.